2019
DOI: 10.4072/rbp.2019.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy analysis (phytoliths, stable isotopes, and C/N) as indicators of paleoenvironmental changes in a Cerrado Site, Southern Brazil

Abstract: Cerrado vegetation is associated with the semi-humid climate of the Central Brazil highlands. The presence of this vegetation in small and sparse areas in Paraná, Southern Brazil, can be associated with its past climate conditions. Paleoenvironmental changes of Cerrado vegetation in the Campo Mourão region (24º06'S-52º23'W) are discussed in this study. The environmental changes were characterized using proxy data that includes stable isotopes and phytolith analyses in peaty sediments. Two drill cores obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…The Cerrado biome occupies 22% of the Brazilian territory and houses a vast and diverse genetic heritage that is unique in the world (Reis;Schmiele, 2019). The Cerrado holds 40% of the endemic plant species and one-third of all Brazilian biodiversity (Luz et al, 2019). Many of the native Cerrado species produce fruits with commercial potential for natural consumption and the production of derivatives such as juices, jellies, and liquors (Neves et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Cerrado biome occupies 22% of the Brazilian territory and houses a vast and diverse genetic heritage that is unique in the world (Reis;Schmiele, 2019). The Cerrado holds 40% of the endemic plant species and one-third of all Brazilian biodiversity (Luz et al, 2019). Many of the native Cerrado species produce fruits with commercial potential for natural consumption and the production of derivatives such as juices, jellies, and liquors (Neves et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Once ferrihydrite is formed, hematite is favoured over goethite with increasing temperature in a drier climate. Therefore, the Hm content observed in the soil profiles G1 and G4 may have been formed under drier past climatic conditions during the Quaternary or older (see section 3.3.1) (Schwertmann, 1971;Behling, 1997;Ker, 1998;Ker and Resende, 1990;Luz et al, 2019). However, Almeida (1979) apud Ker (1998), reported that Fe 3+ contents in the system more than any other factor favour the formation of hematite.…”
Section: Soil Clay Mineralogymentioning
confidence: 93%
“…Maghemite peaks were identified from the upper to deep soil horizons, probably formed from the oxidation of magnetite present in the parent material. The possibility of maghemite formation by transformation of other pedogenetic Fe oxides, such as Hm and Gt under high temperatures in the presence of organic C is not ignored, since, the Holocenic fires in a drier climate were recorded at the studied and nearby areas (see section 3.3.1) (Behling, 1997;Luz et al, 2019).…”
Section: Soil Clay Mineralogymentioning
confidence: 99%
See 2 more Smart Citations